Jurkat T-cell lines exhibit marked genomic instability affecting karyotype, mutational profile, gene expression, immunophenotype and function - Andrew Wilson; Nathaniel Dasyam; Felix O’Hagan; Dianna Farrell; Claire Turner; Anne Jay; Alfonso Schmidt; Rachel Beddow; Tina Lillis; Tom Chin; Rachel Perret; Michelle McCulley; et al. (Scientific Reports)
Abstract The Jurkat cell line, derived from a case of T-cell lymphoblastic leukaemia, is widely employed as a model T-cell for biomedical research, including for the preclinical characterisation of cellular therapies such as chimeric antigen receptor T-cells. Here, we characterised genomic, transcriptomic, and functional features of Jurkat clone E6-1 cells from three different laboratories and compared these with Jurkat E6-1 cells from the American Type Culture Collection (ATCC). We identified marked karyotypic heterogeneity both between and within Jurkat E6-1 populations, confirmed through chromosomal microarray. Whole exome sequencing of each cell population revealed both shared and unique mutational profiles, and transcriptomic profiles varied markedly between Jurkat E6-1 cell populations. Finally, the Jurkat E6-1 cell populations exhibited substantial variations in immunophenotype and cytokine production, which were consistent with the genotypic and transcriptomic changes observed. In summary, we identify substantial genomic heterogeneity both between and within Jurkat E6-1 cell populations, highlighting the genomic instability of this line. These genomic changes were associated with differences in protein expression and cytokine production that may affect functional assays. Our findings highlight the importance of monitoring cell passage number, characterising cell lines, and replacing cell line stocks to assure the accuracy, reproducibility, and translatability of assays employing Jurkat E6-1 cells.